Provenance of terrigenous sediments in the central Bay of Bengal and its relationship to climate changes since 25 ka - Li, Jingrui; Liu, Shengfa; Shi, Xuefa; Chen, Min-Te; Zhang, Hui; Zhu, Aimei; Cui, Jingjing; Khokiattiwong, Somkiat; Kornkanitnan, Narumol (Progress in Earth and Planetary Science, 2020)
Lithogenic grain-size, geochemical elements of core sediments from the central Bay of Bengal (BoB) were analyzed to identify sediment provenance and explore the regional “source-sink” processes since 25 ka. Based on the geochemical compositions of core BoB-88, relative contributions of three end-member sources (Himalayan, Myanmar, Indian Peninsula) were calculated and support the general understanding that Himalayan sources were dominant since the last glacial period, which could reach 70% on average in our study. However, sediments from the Indian Peninsula and Myanmar also contributed nonnegligible materials to the central BoB since 25 ka, especially the former shows an obvious increase since 7.5 ka, which was neglected in the previous studies. To trace the sedimentary processes of different provenance terrigenous materials and reveal their response to climate changes, four typical stages with obvious provenance percent variation, including the Last Glacial Maximum period (LGM), Heinrich 1 (H1), Early Holocene Climate Optimum (EHCO), and mid-late Holocene period, were highlighted and discussed. Sea-level change played a dominant role in the glacial-interglacial scale by controlling the transition of deposition center between the shelf/subaquatic delta and the Bengal Fan, especially for sediment from the Himalayan source, exerting influence on contributions from different provenance end-members between the Holocene and the last glacial period. The opposite directions of the southwest and northeast monsoon current in the BoB have a significant influence on the transfer of the Indian Peninsula and Myanmar materials to the studied core, which led to an increase of up to 11% than the average of the Indian Peninsula and a decrease of up to 9% than the average of the Myanmar source during the Holocene. The balance between sea level (limited transport to the deep sea) and ISM (improved erosion production and output to the BoB) during the mid-late Holocene period maintained the stability of Himalayan source percent. Due to the control of the ISM variations, the Himalayan source showed a decrease of up to 20% and 21% than average during the LGM and H1 period, respectively, and an increase of up to 14% than average during the EHCO. The Myanmar source exhibited fluctuations around the average value during the LGM period, but an obvious increase of up to 21% during the H1 period and a decrease up to 8% during the EHCO, while the Indian Peninsula source percent showed little variations during the LGM and H1, but a decrease of up to 6% during the EHCO. Obvious 1/4 processional and millennial periodic changes (5.0 kyr and 1.1 kyr) of contribution proportions from three end-members provide additional evidences for the climate control on the regional source-sink processes and proved the controlled mechanisms of the orbital parameters and possible influence from the solar activity on millennial scales.

A high resolution record of rare earth element compositional changes from the mud deposit on the inner shelf of the East China Sea: Implications for paleoenvironmental changes - Mi, Beibei; Liu, Shengfa; Shi, Xuefa; Li, Xiaoyan; Pan, Hui-Juan; Chen, Min-Te; Wang, Xuchen (Quaternary International, 2017)
A paleoenvironmental reconstruction of the East China Sea (ECS) is presented using rare earth element (REE) analysis of sediments from Core MZ02, which was retrieved from the inner continental shelf's mud area. The analytic results show that the total REEs in the fine sediment vary between 137.76 μg/g and 231.53 μg/g with an average value of 187.69 μg/g. Obvious changes were found during the process of sedimentation. By comparing with the REE compositions from the potential provenances, the ratios of (La/Sm)ucc and (Gd/Yb)ucc revealed that the sediments were mainly derived from river detrital outputs of the Changjiang (Yangtze River), Minjiang and mountainous rivers from western Taiwan Island. The contributions of terrestrial materials from these three main provenances were controlled by sea level change and the Taiwan Warm Current (TWC)-Chinese Coastal Current (CCC) system, which is mainly driven by the East Asian monsoon. The high sedimentation rate during the transgression period between the late Pleistocene and early Holocene (13000–9800 a B.P.) was caused by a well-proportioned mixed provenance from Changjiang, western Taiwanese rivers and Minjiang sediments, due to the lower sea level and the location of the foreshore-nearshore face. Because of the stronger sediment reworking and erosion at the shelf edge during the early Holocene (9800–7300 a B.P.), the strengthening summer East Asian monsoon transported the Minjiang and western Taiwanese river material northeastward, and it became the main sediment source for fine sediments in the shallow sea region of the ECS, while the Changjiang provided a relatively minor amount of detrital sediment to the shelf. The increasing strength of the TWC might have played an important role in sediment dispersal and deposition on the ECS inner shelf during the period 7300–3500 a B.P., thus mountainous river material became the dominant sediment on the shelf of the ECS. Furthermore, the results indicate that the East Asian monsoon and the weakening of the TWC were linked to an abrupt increase in Changjiang-derived terrigenous detritus material since 3500 a B.P.; the source and sink pattern during this period is consistent with the modern sedimentation environment.
Keywords: East China Sea; Mud deposit; Paleoenvironmental; Provenance; Rare earth element; Sediment

Millennial mode of variability of sea ice conditions in the Okhotsk Sea during the last glaciation (MIS 4–MIS 2) - Vasilenko, Yuriy P.; Gorbarenko, Sergey A.; Bosin, Aleksandr A.; Shi, Xue-fa; Chen, Min-Te; Zou, Jian-jun; Liu, Yan-guang; Artemova, Antonina V.; Yanchenko, Elena A.; Savenko, Mikhail P. (Quaternary International, 2017)
Coarse fraction (CF) content, grain-size distribution, roundness of CF, gravels and pebbles, and examination of surface of pebbles were studied in core LV28-44-4, recovered from the eastern Okhotsk Sea (OS). The age model of the studied core was based on the AMS 14C data, tephrochronology, δ18O benthic foraminifera record, and correlation of peaks of productivity proxies with long-lasted Dansgaard-Oeschger (DO) interstadials. The results show that sea ice was the main transport agent for CF (ice-rafted debris, IRD) in the eastern OS. Published mineralogical studies of clastic material of the OS indicated that the coast of western Kamchatka was the main source of IRD in the eastern OS. We found 19 peaks of IRD, which mostly coincided with DO stadials. The distribution of CF indicates a different pattern of IRD supply during MIS 4, 3, and 2. Comparison of IRD records in the eastern and central parts of the OS allow us to reconstruct millennial changes in ice and wind modes for MIS 4–MIS 2. Significant strengthening of northeastern and eastern winds during DOSs of MIS 3 and of northern and north-western winds during MIS 2 were observed.
Keywords: Ice mode; Ice-rafted debris; Millennial-scale variation; Okhotsk Sea; Wind mode